Pemberdayaan UMKM melalui Pengembangan Minuman Sarabba Instan di Kelurahan Amborawang Laut - Mirza Noor Qolbi; Bayu Irwansyah; Yoga Aprianda Putra; Hendri Wijaya; Jumardi; M. Aldo Saputra; Alya Ananda Putri; Bima Sakti; Nina Pebriani; Nanda Nania Pratiwi; Putri Dwi Melani Maulidya; Siti Aminah (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
This Community Service Program (KKN) was implemented with the aim of enhancing the capacity and independence of Micro, Small, and Medium Enterprises (MSMEs) engaged in the processing of instant Sarabba beverages in Amborawang Laut Village, Kutai Kartanegara District. Sarabba, a traditional beverage from South Sulawesi made from ginger and spices, holds significant local economic potential. However, MSMEs still face several challenges, particularly related to limited marketing strategies, uncompetitive packaging design, and restricted product distribution networks. The implementation methods include participatory observation, in-depth interviews, digital marketing training, business mentoring, packaging design development, and social media-based promotion. The results of the activities showed an increase in the skills and knowledge of SME actors in managing digital marketing, the creation of new packaging designs that are more attractive and in line with market standards, and the expansion of product distribution reach beyond the Amborawang Laut area. The tangible impact of this program is the increased competitiveness of local SMEs while strengthening the sustainability of the community's economy based on traditional food potential. This program underscores that collaboration between students and the community can serve as a catalyst for strengthening the creative economy, with sustainability supported through ongoing mentoring and the strengthening of networks among SMEs.